`ln(x) - ln(2) = 0` Solve for `x`.

2 Answers

Educator Approved

Educator Approved
loves2learn's profile pic

loves2learn | (Level 3) Salutatorian

Posted on

`ln(x)=ln(2) `

Therefore,

`x=2 `

Educator Approved

Educator Approved
loves2learn's profile pic

loves2learn | (Level 3) Salutatorian

Posted on

Whenever you need to solve for a variable, you need to isolate it. Therefore, you should first add `ln2 ` to both sides.

Therefore,

`lnx=ln2 `

Now, it would be tricky to solve this problem if you don't know any log rules. However, there is a rule that states,

Given,

`lna=lnb `

Then,

`a=b `

The same thing works here. `x=a ` and `b=2 `

Therefore, `x=2 `